Assessment of quality of life and its determinants among the elderly residing in a rural area of Faridabad: A cross-sectional survey - Ekta Gupta; Shweta Goswami; Vaishali Aggarwal; Mitasha Singh; Rashmi Agarwalla (Indian Journal of Community and Family Medicine, 2021)
Introduction: Population aging as a result of demographic transition has brought into focus issues pertaining to health status of elderly. We aimed to assess different domains of quality of life (QoL) and its determinants among the elderly population of a rural area of Faridabad. Material & Methods: A community-based cross-sectional study was carried out among 300 elderly people aged 60 years and above from October 2018 to January 2019 in village Pali of Faridabad, Haryana. The World Health Organization QOL-BREF scale was used for the assessment of QoL. Results: The study included 44% males with a mean age of 67.1 ± 7 years. The mean QOL score was highest in psychological domain (63.26 ± 18.48), followed by environmental domain (62.64 ± 16.23), physical domain (60.58 ± 19.24), and lowest in social domain (59.33 ± 17.81). Conclusion: Physical domain of QoL was significantly better in nondiseased elderly, while social domain was not significantly affected by morbidities or health-seeking behavior. Overall, QoL was fair to good. Determinants of good QoL included social as well as economic characteristics such as higher education, sex, and the absence of chronic disorders.